IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI 1KOTO BALINGKA KABUPATEN PASAMAN BARAT - Kusnindra, Hari; Atmazaki, Atmazaki; Hafrison, Mhd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTThis study aims to reveal three problems regarding the implementation of the scientific approach in Indonesian subjects Curriculum 2013. First, the application of the scientific approach. Secondly, there are obstacles in the implementation of learning. Third, the follow-up done by the teacher in overcoming the constraints of learning. This research was conducted with qualitative research using descriptive methods. Data collected in this study using the method of observation, documentation, and interviews. The data in this study were analyzed through data reduction, data presentation, and drawing conclusions. The subjects in this study were Indonesian language teachers at SMPN 1 Koto Balingka, West Pasaman Regency. The results showed that in learning activities using a scientific approach the teacher was doing well. In the learning process the teacher has explained the five stages of learning by using a scientific approach, starting from observing, holding, reasoning, trying, to communicating. The results of this study also show the results that there are still obstacles faced by teachers in the process of implementing learning, for example, constrained by supporting facilities and infrastructures in learning. In the learning process the teacher has done step 5 M and has a role as a facilitator so that students are actively involved in learning. In general, learning activities with a scientific approach have been going well, but there are still obstacles faced by teachers in their implementation. Kata Kunci: Implementasi, Pendekatan Saintifik, Pembelajaran              Bahasa Indonesia